(3UfGYI GdGSWQdGHs - (3eMeO GdYQHj Hf YHO GdQMef eaQL GdTaTGhfj GdeQGQs ((3bGSe Hf YHO Gddg Hf bGSe Hf YdhT GdjGdUhfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY GdSehGJ hRjfgG HGdchGcH GdfjQGJ hHYO , adeG cGf ef CLd GdUfGFY UfGYI GdESWQdGH s
(3BNQgG (B:s
(3hcPdc JYQa GQJaGY fUa fgGQ HdOc HGJaGY fUa GdfgGQ ai GdYQVjf GfJgJ GdQSGdI s
(3HgG CTcGds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs